Genotype x Environment Interaction for the Height Growth in Prosopis Cineraria (L.) MacBride - Solanki, K R; Jindal, S K; Muthana, K D; Kackar, N L (Annals of Arid Zone, 2016)
Genotype x environment interaction in Prosopi cineraria for the height growth was studied for six years (1978 to 1983). Significant differences were present among nine trees studied. Increase in height growth was found to be directly related to the total rainfall of the preceding year. The tree type JU 4 showed high adaptability to all the environments and was stable too.